2013
DOI: 10.1002/grl.50438
|View full text |Cite
|
Sign up to set email alerts
|

Stress tensor changes related to fluid injection at The Geysers geothermal field, California

Abstract: [1] Studying variations of the stress field in reservoirs caused by massive fluid injection is important toward an improved understanding of geomechanical processes involved. We report on spatio-temporal variations of the local stress tensor orientation at The Geysers geothermal field, California. We apply two stress inversion methods with detailed uncertainty assessments using a selection of events recorded between 2007 and 2012. Our results clearly indicate variations in the orientation of the principal stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 22 publications
8
88
4
Order By: Relevance
“…Another relevant point mentioned by Johnson (2014b) is the likelihood that cracks in close proximity may interact. Given the highly fractured subsurface with complex conjugate fault geometries and stress heterogeneity from nearby weakened fault zones, it may be possible that shear slip occurs such that critically stressed fractures, favorably oriented for failure, are reactivated (Majer and McEvilly, 1979;Bufe et al, 1981;McLaughlin, 1981;Eberhart-Phillips and Oppenheimer, 1984;Oppenheimer, 1986;King et al, 1994;Cladouhos et al, 2009;Martinez-Garzon et al, 2013). Two other nearby events, event 27 (27 December 2004 M w 4.31, depth 3.71 km) and event 46 (29 June 2011 M w 3.26, depth 1.76 km) have large isotropic components of 49% and 52%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant point mentioned by Johnson (2014b) is the likelihood that cracks in close proximity may interact. Given the highly fractured subsurface with complex conjugate fault geometries and stress heterogeneity from nearby weakened fault zones, it may be possible that shear slip occurs such that critically stressed fractures, favorably oriented for failure, are reactivated (Majer and McEvilly, 1979;Bufe et al, 1981;McLaughlin, 1981;Eberhart-Phillips and Oppenheimer, 1984;Oppenheimer, 1986;King et al, 1994;Cladouhos et al, 2009;Martinez-Garzon et al, 2013). Two other nearby events, event 27 (27 December 2004 M w 4.31, depth 3.71 km) and event 46 (29 June 2011 M w 3.26, depth 1.76 km) have large isotropic components of 49% and 52%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These include potential weak gouges on the fault, dynamic weakening (Melosh 1996) or high pore fluid pressure as found for the 2000 earthquake in the central SISZ Bonafede et al 2007). Changes of pore fluid pressure can also have potential effects on the orientation of S H , as shown by Martínez-Garzón et al (2013). Holt et al (2013) observed a ratio of stress drop to background shear stress of 0.4 for the central segment of the 2010 M W 7.1 Darfield earthquake in New Zealand, if the apparent stress rotation was caused by the earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the variability of the mechanisms we observe must be due to additional factors. Nolen-Hoeksema and Ruff (2001) proposed three mechanisms that may produce seismicity during hydrofracturing: (1) tensile fracturing at the tip of the propagating fracture, (2) pressure leak-off into pre-existing fractures that intersect the propagating hydrofracture, resulting in their weakening and shear failure (e.g., Rutledge et al, 2004), or (3) slip along pre-existing fractures near the fracture tip induced by stress perturbations associated with fracture propagation (Martínez-Garzón et al, 2013;Warpinski and Branagan, 1989). In our case, pure tensile fracturing (mechanism 1) can be excluded for the observed double-couple events.…”
Section: Comparison To Overcoring Stress Measurementsmentioning
confidence: 99%